Nutritional intervention alleviates T cell exhaustion and empowers anti-tumor immunity - Xu, Yuqi; Yuan, Wenhui; Li, Ke; Li, Peng (Frontiers in Immunology, 2025)
T cells are central mediators of adaptive immunity, playing a pivotal role in eliminating pathogens and tumor cells. In the context of chronic infections and cancer, however, persistent antigenic stimulation drives T cells into a state of exhaustion characterized by diminished effector function, sustained expression of inhibitory receptors, and profound metabolic reprogramming. Emerging evidence indicates that T cell exhaustion is not irreversible and can be alleviated through immune checkpoint blockade, such as targeting PD-1. Moreover, increasing attention has been directed toward the role of intracellular metabolic pathways in shaping T cell fate and function. Strategies aimed at enhancing nutrient availability and metabolic fitness offer an additional avenue to restore T cell activity. This review highlights recent advances in reversing T cell exhaustion through immune checkpoint inhibitors and nutritional interventions, providing novel insights into the precision and personalization of cancer immunotherapy.